(3GdMOjK GdVYja hCKQg aj GdCMcGes (3OQGSI JWHjbjI aj cJGH fjd GdChWGQ ddEeGe GdThcGfj (B: (3cJGH GdYHGOGJ hGdeYGedGJ (B/s - (3GdYjOQhS, Rjf eMeO MSjfs; (3GdThcGfj, eMeO Hf Ydj Hf eMeO,s 1173-1250 (3g`(B.s; (3GHf JjejI, YHO GdSdGe Hf YHO Gddg Hf GdNVQ,s (3J(B. 652 (3g`(B.s ((3GdbGgQI (B:s (3OGQ GdHUGFQ,s, 2011)
(3OQGSI dcJGH fjd GdChWGQ ddEeGe GdThcGfj(B.s
Keywords: (3GdMOjKs -- (3ESfGO VYjas